2021
DOI: 10.31236/osf.io/cfvzu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex Difference in Hip Adduction during Running: Influence of Hip Abductor Strength, Activation, and Pelvis & Femur Morphology

Abstract: Purpose: To examine the influence of hip abductor strength, neuromuscular activation, and pelvis & femur morphology in contributing to sex differences in hip adduction during running.Methods: Fifteen female and 14 male runners underwent strength testing, instrumented overground running (e.g., kinematics and muscle activation), and computed tomography scanning of pelvis and femur. Morphologic measurements included bilateral hip width to femur length ratio, acetabulum abduction, acetabulum anteversion, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In patient with increased AVA but normal foot progression angle, Passmore et al [29] showed that higher gluteus medius muscle forces are needed for walking with the patient-speci c femoral geometry compared to a normal, typical geometry. Several other studies [70][71][72][73] investigated the relationship between femoral geometry and muscle strength. To the best of our knowledge, no studies showed a clear relationship between the femoral geometry (combined AVA and NSA), muscle strength and gait pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In patient with increased AVA but normal foot progression angle, Passmore et al [29] showed that higher gluteus medius muscle forces are needed for walking with the patient-speci c femoral geometry compared to a normal, typical geometry. Several other studies [70][71][72][73] investigated the relationship between femoral geometry and muscle strength. To the best of our knowledge, no studies showed a clear relationship between the femoral geometry (combined AVA and NSA), muscle strength and gait pattern.…”
Section: Discussionmentioning
confidence: 99%